(untitled) - NOVITANINGRUM, ANGELLA (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstrak MenulisadalahsalahsatuketrampilandalamBahasaInggris yang harusdikuasai. Hal iniberhubungandengantujuanpengajaranBahasaInggrisyaituuntukmengembangkankemampuanberbahasadalambentukberbicaradanmenulis. Selainitu, menulisdikenalsebagaiketrampilanBahasaInggris yang paling sulitbagisiswa. Merekamerasamenulismembingunkankarenatidakmempunyai ide dantakutuntukmembuatkesalahandalammenulis. Ditambahlagi, ketidaksukaanmenulis yang ditunjukkanolehsiswajugamemberipengaruh yang burukpadakeberhasilanmerekadalammenulis. Olehkarenaitu, guru harusmempunyaistrategidalampengajaranmenulisuntukmembantumasalahsiswa. Hal inipentingdalammemilihstrategi yang sesuaidanmenarikuntukmemotivasidanmenarikmerekauntukmeningkatkankemampuanmenulis. Story pyramid adalahsalahsatustrategi yang dapatdigunakandalampengajaranmenulis. Strategiiniadalahaktifitas yang dilakukansebelummenulis yang mendeskripsikaninformasipentingdarisebuahcerita, antara lain karakterutama, tempatkejadiandankejadianutamadalamalurcerita. Strategiinimembantuuntukmengumpulkandanmengorganisasikan ide secarajelassebelummenulisdimulai. Tujuandaripenelitianiniadalahmendeskripsikanpenerapan story pyramid dalampengajaranmenulisnaratifteksuntuksiswakelasdelapan, responsiswaterhadappenerapan story pyramid danhasiltugastulisansiswaselamapenerapan story pyramid. Penelitianiniadalahpenelitiandeskriptifqualitatif. Subjekdaripenelitianiniadalah 35 siswapadakelas 8-11 SMPN 2 Sidoarjo. Penelitianinimenggunakantigainstrrumenpenelitianuntukmemperoleh data, yaitulembarobservasi, quesionerdanhasiltugastulisansiswa. Berdasarkanhasildaripenelitian, hasil yang pertamadiperolehdenganmenggunakanlembarobservasi. Hal inimenunjukkanbahwapenerapan story pyramid dalampengajaranmenullisnaratifteksberjalandenganbaik. Prosedurdari story pyramid yang telahdilakukanoleh guru di dalamkelassesuaidenganteoridandilakukansecaraurut. Guru jugamemberikanpenjelasan yang jelassebelummenggunakan story pyramid dalampengajranmenulisnaratifteks. Hasil yang keduaadalahresponsiswaterhadappenerapan story pyramid. Data diperolehdariquesioner. Quesionerdiberikankepadasiswa yang tediridarisepuluhpertanyaandalambentukpilihanganda. Hal inimenunjukkanbahwahampirsemuasiswatertarikdalampenerapan story pyramid. Data yang terakhiradalahhasiltugastulisansiswa. Hasiltugastulisansiswa di analisisdenganmenggunakan ESL composition profile yang mempunyai lima kriteria, yaituisi, organisasi, penggunaanbahasa, kosa kata danmekanismetulisan. Kesimpulanya, story pyramid dapatdigunakandalampengajaranmenulisteksnaratifuntuksiswakelasdelapan. Story pyramid bergunauntukmembantusiswamengingat ide yang akanmerekadeskripsikansesuaidenganmaksudmereka. Kata Kunci: Story Pyramid, Menulis, TeksNaratif, ResponSiswa Abstract Writing is one of the English skills which has to be mastered. It is related to the purpose of teaching English, that is, to develop the linguistic competence both in spoken and written form. Moreover, writing is known as the most difficult skill in English for the students. They confused to start writing because they have no any ideas to write and afraid to make mistakes in their writing. In addition, the dislike of writing that is shown by the students also gives bad effect to their achievement in writing. That is why, the teacher should have strategy to help the students’ problem. It is important to choose an appropriate and interesting strategy to motivate and attract the students in improving their writing skill. Story pyramid is one of strategies that can be used in teaching writing. It is a pre-writing activity that describes important information from a story such as the main character, the setting and the major events in the plot. It helps to generate and organize the ideas clearly before it starts to write. The aims of this research are to describe the implementation of story pyramid in teaching writing narrative text for eighth graders, the students’ responses towards the implementation of story pyramid and the students’ writing task result during the implementation of story pyramid. This research is a descriptive qualitative research. The subjects of this research are 35 students in 8-11 of SMPN 2 Sidoarjo. It uses three research instruments to gain the data, those are observation checklist, questionnaire, and students’s writing task result. Based on the research finding, the first result was collected by using observation checklist. It showed that the implementation of story pyramid in teaching writing narrative text run well. The procedures of story pyramid that the teacher had been applied in a classroom appropriate with the theory and well organized. She also gave clear explanation before using story pyramid in teaching writing narrative text. The second result was students’response towards the implementation of story pyramid. The data were gotten from questionnaire. It was given to the students which consists of ten questions in the form of multiple choice. It showed that almost all of the students were interested in the implementation of story pyramid. The last result was students’writing task result. It was analyzed by using ESL composition profile which has five criteria, those are: content, organization, language use, vocabulary and mechanics. In conclusion, story pyramid can be used in teaching writing narrative text for eighth graders. It is useful to help the students to keep their ideas that they want to describe as their intention. Key Words: Story Pyramid, Writing, Narrative Text, Students’ response